Facile Fabrication of TiO2/SrTiO3 Composite Nanofibers by Electrospinning for High Efficient H2 Generation. Issue 3 (9th November 2012) - Bai, Hongwei; Liu, Zhaoyang; Sun, Darren D.
Abstract : Using electrospinning, specially prepared Ti and Sr precursor TiO2 /SrTiO3 composite nanofibers were successfully fabricated. This would ensure the close and uniform contact between TiO2 and SrTiO3, which significantly contributes to the electrons transfer at the interface between the two semiconductors with different band gaps. Meanwhile, the long fibrous structure of TiO2 /SrTiO3 composite nanofibers would further ease the electron transfer, enlarge the specific surface area, and enhance the light absorption capability thus leading to the improvement of photocatalytic efficiency. Because of the above‐mentioned advantages, the TiO2 /SrTiO3 composite nanofibers exhibited higher photocatalytic H2 generation efficiency over bare TiO2 nanofibers in a water/methanol sacrificial reagent system under the irradiation of UV light.